Regulatory role of S1P and its receptors in sepsis-induced liver injury - Wang, Bin; Wu, Xiaoyu; Cheng, Jiangfeng; Ye, Junming; Zhu, Hongquan; Liu, Xiaofeng (Frontiers in Immunology, 2025)
As an immune and metabolic organ, the liver affects the progression and prognosis of sepsis. Despite the severe adverse effects of sepsis liver injury on the body, treatment options remain limited. Sphingosine-1-phosphate (S1P) is a widely distributed lipid signaling molecule that binds to five sphingosine-1-phosphate receptors (S1PR) to regulate downstream signaling pathways involved in the pathophysiological processes of sepsis, including endothelial permeability, cytokine release, and vascular tone. This review summarizes current research on the role of S1P in normal liver biology and describes the mechanisms by which changes in S1P/S1PR affect the development of liver-related diseases. At the same time, the pathological processes underlying liver injury, as evidenced by clinical manifestations during sepsis, were comprehensively reviewed. This paper focused on the mechanistic pathways through which S1P and its receptors modulate immunity, bile acid metabolism, and liver-intestinal circulation in septic liver injury. Finally, the relationships between S1P and its receptors with liver inflammation and metabolism and the use of related drugs for the treatment of liver injury were examined. By elucidating the role of S1P and its receptor in the pathogenesis of sepsis liver injury, this review established a molecular targeting framework, providing novel insights into clinical and drug development.